Pengaruh Desain Interior dan Lokasi Pada Café Exquise Patisserie Terhadap Keputusan Pembelian (Studi Kasus Mahasiswa Bhayangkara Jakarta Raya Angkatan 2022) - Dhanisya Wiaam Sausan; Muthia Aminie; Cahyadi Husada; Jumawan Jumawan (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
To what degree do factors like location and interior design influence consumer choices? That is the question this research seeks to answer. The author of this piece of study believes that readers and writers will be able to deduce how factors like location and interior design impact purchasing decisions. This research employs a quantitative approach by surveying 89 members of the Bhayangkara University Jakarta Raya class of 2022 and analyzing their responses using SPSS model 26. The researcher is eager to find out how big of an impact the café's location and interior design have on customers' decisions to make a purchase, thus this study is quite important.